Permanent indwelling catheter for the management of refractory malignant pericardial effusion - Frederik Schultz Pustelnik; Christian B. Laursen; Arman Arshad; Ahmed Aziz (European Clinical Respiratory Journal, 2022)
In this case report, we describe the novel use of a permanent indwelling catheter (PiC) in the management of refractory malignant pericardial effusion (PE). The patient had disseminated lung cancer and was hospitalised repeatedly with circulatory collapse due to malignant PE despite treatments with pericardiocentesis (PCC) and a pericardial window (PW). The PiC was inserted as a last resort with no complications and was a mediator of pericardiodesis (PCD), resulting in the cease of PE. The PiC could subsequently be removed, and there was no relapse of PE.